A note on the potential designation of the mediterranean sea as a sulphur emission control area. (November 2020) - Testa, David
Abstract: This note provides an overview of the progress that has been registered towards a potential designation of the Mediterranean Sea as a Sulphur Emission Control Area (SECA). It also examines a number of legal and practical issues – particularly in relation to enforcement – that are likely to be encountered should a stricter sulphur limit for marine fuels be adopted in relation to the Mediterranean. The note argues that while previous experience with the four ECAs that have been designated to date can be instructive, the Mediterranean Sea region has a number of peculiarities that need to be accounted for.